PERSENTASE HATI, JANTUNG, DAN LEMAK ABDOMINAL BROILER DENGAN PEMBERIAN SERBUK PINANG DALAM RANSUM - Nilawati Nilawati; A Gustian (Wahana Peternakan, 2023)
The purpose of this study was to identify the percentage of liver, abdominal fat and heart of broilers by giving areca nut powder in the ration. The study was conducted on 200 DOC broiler reared up to 28 days old. This study used a completely randomized design with 4 treatments and 5 replications. The treatment given was the addition of areca nut powder in the broiler ration. The treatment given consisted of control, addition of 1.5%, 3% and 4.5% areca nut powder. Variables in this study include liver percentage, abdominal fat percentage and broiler heart percentage. The results of this study indicate that the administration of areca nut powder has a significant effect (p<0.05) on the percentage of broiler abdominal fat and does not show a significant effect (p>0.05) on the percentage of broiler liver and heart percentage. The results of this study found that the addition of areca nut powder at 1.5% showed the best results on the percentage of liver, abdominal fat percentage and broiler heart percentage compared to controls, levels of 3% and 4.5%. Keywords: Areca Nut Powder, Broiler, Liver Percentage, Abdominal Fat Percentage, and Broiler Heart Percentage.